1987
DOI: 10.1200/jco.1987.5.8.1232
|View full text |Cite
|
Sign up to set email alerts
|

Phase I trial of taxol given as a 24-hour infusion every 21 days: responses observed in metastatic melanoma.

Abstract: Taxol, a plant product, has significant activity against certain rodent and human xenograft tumors. It promotes microtubule assembly in vitro, in contrast to vinca alkaloids, which inhibit assembly. In this phase I study, taxol was administered as a 24-hour continuous intravenous (IV) infusion in 65 courses to 26 patients. A premedication regimen of dexamethasone, cimetidine, and diphenhydramine was used to prevent the acute hypersensitivity reactions observed in previous studies of taxol. Only one episode of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
90
1
3

Year Published

1994
1994
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 266 publications
(98 citation statements)
references
References 12 publications
4
90
1
3
Order By: Relevance
“…The paclitaxel levels reached a maximum at the end of the 24-finding was that the paclitaxel levels increased in the postinfusion CSF up to a maximum on Day 3 and then dehour infusion, which is similar to results published in Phase I studies. 1,9 clined, which is consistent with a diffusion phenomena into and out of the CSF. Paclitaxel levels were also detected in malignant ascitic and pleural fluids with this Detection of Paclitaxel Levels in Human Cerebrospinal, method (Table 2).…”
Section: High Performance Liquid Chromatographysupporting
confidence: 59%
See 1 more Smart Citation
“…The paclitaxel levels reached a maximum at the end of the 24-finding was that the paclitaxel levels increased in the postinfusion CSF up to a maximum on Day 3 and then dehour infusion, which is similar to results published in Phase I studies. 1,9 clined, which is consistent with a diffusion phenomena into and out of the CSF. Paclitaxel levels were also detected in malignant ascitic and pleural fluids with this Detection of Paclitaxel Levels in Human Cerebrospinal, method (Table 2).…”
Section: High Performance Liquid Chromatographysupporting
confidence: 59%
“…This curve shows the same S-shaped pattern as free paclimodification of previously described procedures. 1,11 To prepare samples for high pressure liquid chromataxel diluted first in ethanol and subsequently diluted into blocking buffer, and revealed an even greater sentography (HPLC) analysis, 0.5 mL of sera was combined with 1 mL acetonitrile, then centrifuged (for 10 sitivity in detecting drug levels. Complete inhibition of MoAb binding is seen again at a 1 mM concentration minutes at 10,000 RPM).…”
Section: Competitive Immunoradiometric Assaymentioning
confidence: 99%
“…To further evaluate and expand drug sensitivity studies associated with HER-2/neu overexpression, we developed an in vivo chemotherapeutic drug sensitivity assay which utilized serial measurements Table 1 Eect of HER-2/neu overexpression on sensitivity of human breast cells to chemotherapeutic agents in vitro (Gormley et al, 1979) 5.6 (Robert et al, 1982) 1000 (MacMillan et al, 1978) 940 (Wiernik et al, 1987) 10.6 (Cohen et al, 1986) 400 (Nelson et al, 1980) 50…”
Section: Eect Of Her-2/neu Expression On Chemosensitivity Of Breast Amentioning
confidence: 99%
“…It has been reported that neuropathy associated with paclitaxel by a 24-h injection is dependent upon total cumulative dosage, and no known risk factors have been identified (Wiemik et al, 1987;Chaudhry et al, 1994). Little information is available on the pharmacokinetics and this toxicity.…”
mentioning
confidence: 99%